The Association between Remarriage and HIV Infection : Evidence from National HIV Surveys in Africa - de Walque, Damien (2012)
The literature shows that divorced, separated, and widowed individuals in Africa are at significantly increased risk for HIV. Using nationally representative data from 13 countries in Sub-Saharan Africa, this paper confirms that formerly married individuals are at significantly higher risk for HIV. The study goes further by examining individuals who have remarried. The results show that remarried individuals form a large portion of the population - usually larger than the divorced, separated, or widowed - and that they also have higher than average HIV prevalence. This large number of high-risk remarried individuals is an important source of vulnerability and further infection that needs to be acknowledged and taken into account in prevention strategies.